Colombian reference growth curves for height, weight, body mass index and head circumference (2015)
Aim Published Growth studies from Latin America are limited to growth references from Argentina and Venezuela. The aim of this study was to construct reference growth curves for height, weight, body mass index (BMI ) and head circumference of Colombian children in a format that is useful for following the growth of the individual child and as a tool for public health. Methods Prospective measurements from 27 209 Colombian children from middle and upper socio‐economic level families were processed using the generalised additive models for location, scale and shape (GAMLSS ). Results Descriptive statistics for length and height, weight, BMI and head circumference for age are given as raw and smoothed values. Final height was 172.3 cm for boys and 159.4 cm for girls. Weight at 18 years of age was 64.0 kg for boys and 54 kg for girls. Growth curves are presented in a ± 3 SD format using logarithmic axes. Conclusion The constructed reference growth curves are a start for following secular trends in Colombia and are also in the presented layout an optimal clinical tool for health care.